Comparison of User Pairing Methods for NOMA in Beamforming Training within 802.11ad WLANs - Choi, Seonjoo; Baek, Hoki; Lim, Jaesung (International Conference on ICT Convergence, 2024)
Beamforming training (BFT) is crucial for communication performance in the mmWave environment. A suitable multiple access technique is essential for enabling multiple users to perform BFT simultaneously. Therefore, non-orthogonal multiple access (NOMA) is a potential candidate for enabling multiple users to perform BFT. A user pairing method is necessary for performing BFT simultaneously with NOMA. We assessed the user pairing probability when applying various user pairing methods and identified the most appropriate user pairing strategy based on the network environment.
Keywords: 802.11ad; Beamforming training; Communication performance; Mm waves; Multiple access; Multiple user; Non-orthogonal; Non-orthogonal multiple access; Pairing method; User pairing; 802.11ad; beamforming training; NOMA; user pairing